Scientific prerequisites for the design of environmentally compatible industrial buildings in the conditions of Uzbekistan - Abdukodirova Nigina Shuxratali qizi (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
Objective. The environmental situation of the Republic of Uzbekistan is extremely worrying. Soil, air and water are contaminated. The extraction of deposits and building materials is carried out irrationally, and scientifically based approaches to the placement of new production forces and industrial enterprises, as well as their design, are not in demand. The purpose of the study is to propose conceptual principles for the construction of a building that combines a holistic expression of the production environment and environmental infrastructure, which, when designing production enterprises, it is possible to change industrial buildings to a standstill, that is, to the desired side, looking at them as an ecological object. Methods. The ecological purity of production enterprises is considered as a complex task, that is, to create a harmonious and comfortable environment for the productive work of a person; to establish waste-free use of energy resources in the form of a closed system; to ensure that architectural and building forms (building elements) are harmonious and proportional to the natural environment Results. Currently, the spiritual deterioration of technology begins in 2-3 years and is at most 5-7 years. And the physical deterioration of industrial buildings and structures will be for 50-70 years or more.In order for the designed buildings to be able to respond to calls for time, it is necessary to ensure that their spatial-constructive and architectural solutions can accommodate the level of progress of science, technique and technology for the next 50-70 years. For this, it is proposed to plan in advance the problem of spiritual deterioration. Conclusion. Environmental components of ecological buildings are systematically approached in terms of quality, complex requirements for the use of the environment and nature are observed during the construction and use of buildings, a typological series of multifunctional energy-efficient buildings with innovative architectural-construction and engineering-technical solutions is created, an environment with maximum aesthetic appeal organically linked with, architectural compositions consisting of building and technological modules of different plans and heights are created.